The Contestation of Authority in Islamic Marriage Law Indonesia - Nasir, Muhammad; Aniza, Aniza; Muzakkir, Muzakkir; Roni, Muhammad (Institut Agama Islam Negeri Curup, 2023)
This article describes the contestation between government authorities and religious scholars (ulemas) in the creation of marriage laws in Aceh. The research data were derived from observations, interviews, and documentation, constituting a qualitative study with a theoretical framework based on the relationship between the state and religion, as well as the Theory of Legal Certainty, employing a socio-legal approach. The findings of this study illustrated that the authority of the ulemas was manifested through the issuance of fatwas by Acehnese ulemas, which also operated in society illegally. On the other hand, government authority was realized through the enactment of marriage laws and the Islamic Criminal Code (KHI) implemented by government institutions. The fragmentation and contestation of these authorities occurred following the enactment of the Special Autonomy Law, which granted authority to the ulemas to issue fatwas. As a result, dualism in marriage laws emerged in Aceh, leading to various issues such as legal uncertainty, a lack of trust in state institutions, and the proliferation of illegal marriages in Aceh. Additionally, Acehnese ulemas sought to establish their own local laws for Aceh, independent of national marriage laws. Therefore, it is imperative to establish Aceh's marriage laws through regional regulations (qanun) while accommodating the fatwas issued by Acehnese ulemas.